2019
DOI: 10.1029/2019jc015466
|View full text |Cite
|
Sign up to set email alerts
|

High‐Frequency Tide‐Surge‐River Interaction in Estuaries: Causes and Implications for Coastal Flooding

Abstract: Tide-surge interaction creates perturbations to storm surge at tidal frequencies and can affect the timing and magnitude of surge in tidally energetic regions. To date, limited research has identified high-frequency tide-surge interaction (>4 cycles per day) in coastal areas, and its significance in fluvial estuaries (where we consider it tide-surge-river interaction) is not well documented. Water level and current velocity observations were used to analyze tide-surge-river interaction at multiple tidal and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Flooding due to tide-surge-river interaction can be even more pronounced in short, relatively straight and shallow estuaries. High-frequency tide-surge-river interaction, which is caused by friction and resonance, amplified the wind and pressure-driven (low-frequency) storm surge to over 2 m during a storm event at the head of the Penobscot River (Spicer et al 2019), which is adjacent to the Bagaduce River Estuary.…”
Section: Storm Surgementioning
confidence: 99%
See 1 more Smart Citation
“…Flooding due to tide-surge-river interaction can be even more pronounced in short, relatively straight and shallow estuaries. High-frequency tide-surge-river interaction, which is caused by friction and resonance, amplified the wind and pressure-driven (low-frequency) storm surge to over 2 m during a storm event at the head of the Penobscot River (Spicer et al 2019), which is adjacent to the Bagaduce River Estuary.…”
Section: Storm Surgementioning
confidence: 99%
“…If this level of surge coincides with high tide, this could impose extreme loads on the mooring lines and anchor systems. Predictions from the National Oceanic and Atmospheric Association's Extratropical Storm Surge (ETSS) model during large tide-surge-river interaction events revealed significant (~1.6 m) discrepancies between predicted and observed total surge levels (Spicer et al 2019). The ETSS model only predicts wind-and pressure-driven storm surge and does not account for tide-surge-river interaction, which suggests that actual flooding may far exceed anticipated surge levels.…”
Section: Storm Surgementioning
confidence: 99%
“…Their work further suggests the tide-CDR and surge-CDR interactions both induce asymmetries in the water level and the interactions are mainly caused by the quadratic bottom friction. Spicer et al (2019) and Spicer et al (2021) collected observations in Maine estuaries during "windstorms" and pointed out the TSRI to be the dominant mechanism contributing to upstream surge amplification (which is estimated to be exceeding 1m and more than double than nontidal forcing induced surges). By testing different combinations of the atmospheric forcing effect on generating the extreme water levels via non-stationary tidal harmonic analysis (Matte et al, 2013), the mechanism to generate TSRI is found to be related to the increased mean flow and frictional energy from wind forcing (Spicer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the relative importance of TSI and TRI to the overall TSRI during compound flooding events has not been well documented. Spicer et al (2019) raised attention to the importance of distinguishing how non-linear TRI varies from TSI by using a non-stationary tidal analysis method to account for non-linear interactions. The methods to analyze tidal constituents of a tidal record have been well summarized by Hoitink and Jay (2016), based on assumptions of either stationary or non-stationary environments.…”
Section: Introductionmentioning
confidence: 99%
“…Unlocking our understanding of nature-based coastal protection within estuaries is vital because these environments are particularly at risk of increased storm-driven surge and wave ooding; estuaries often have low-lying adjacent land 7,[32][33][34][35] , act as an interface between ood waters from coastal surge and riverine ooding 29,36,37 , and form natural tidal and storm funnels which magnify and transfer surge effects up-stream 36,38 , threatening inland human settlements and infrastructure 39,40 . Yet despite the enhanced ooding risk in estuaries, natural coastal protection features -such as extensive saltmarshes which typify many estuaries worldwide -can moderate the effects of coastal storms on ooding 25,30 and potentially offer signi cant nature based coastal protection services 26,41 .…”
Section: Introductionmentioning
confidence: 99%